A Thematical Study to Review the Impact of Consumer Characteristics on Online Purchasing Intention in E-commerce - G. P. H. Kandambi; W. M. Janaka I. Wijayanayake (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
The summary of this article offers a thorough analysis of earlier research on the influence of customer traits seen in the idea of online purchasing intention. This will establish the foundation for identifying the research gap in this area and its potential for more study. The key academic disciplines that have a direct impact on this setting are applied sciences, business management, information communication technology, and marketing. The data from the gathered articles were identified, examined, and reported on using a thematic analysis approach in this paper. Core articles were found from one hundred twelve (n=112) leading and peer-reviewed conferences and indexed journals between the years 2010 and 2015 for the evaluation. Consumer characteristics such as personality characteristics (Theme1) with six (n=6) sub-themes, demographic (Theme2) with five (n=5) subthemes, perceived characteristics (Theme 3) with nine (n=9) subtheme and purchase intention (Theme4) with three (n=3) subthemes were identified. This analysis considered the types of relationships and their impact, the effects of moderating variables, and the mediating effect on the relationship between the independent variable and the dependent variable. When several major variables are compared, the results are contradictory. It is necessary to re-examine those variables for additional confirmation. Several factors were identified and classified as Consumer, Retailer, Medium, and External environment characteristics. The evaluation results indicate the need for a comprehensive integrated model that investigates a broader range of variables. As a result, different countries and nations with varying characteristics, behaviours, and socioeconomic backgrounds should be investigated separately in the future.